Characterisation of the HIV-1 subtype C Env gene and the expression of the Env protein from selected isolates in mammalian cells - De Villiers, Tania (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.